Paleoradiological and scientific investigations of the screaming woman mummy from the area beneath Senmut’s (1479–1458 BC) Theban tomb (TT71) - Saleem, Sahar N.; El-Merghani, Samia (Frontiers in Medicine, 2024)
Introduction: The Screaming Mummy of Cairo Egyptian-Museum Store, is an anonymous woman with a wide-open mouth coded as CIT8, discovered beneath Theban Tomb 71 (TT71) which is the burial site of Senmut's relatives, the architect of 18th-Dynasty Queen Hatschepsut (1479-1458 BC). The study aims to evaluate if combining CT with scientific investigations and archaeological data of the Screaming Mummy CIT8 will reveal information about its physical appearance, health, cause of death, and mummification. Methods We CT-scanned the mummy and created reconstructed images. Scanning-Electron-Microscope (SEM), Fourier-Transform-Infrared-Spectroscopy (FTIR), and X-ray-Diffraction-Analysis (XRD) were used to investigate mummy skin, hair, and wig samples. We compared our findings to previous data. Results CT estimated the age of death to be 48.1 years  14.6 based on the pubic symphyseal surface. CT detected mild-to-moderate teeth attrition, and joints degeneration. The desiccated brain and viscera remained in situ. FTIR revealed the wig is formed of midrib date palm that shows in CT as spiral low density fibres. The wig fibres are partially coated with a thick substance that is inspected as black consolidation and identified as crystalline by XRD, comparable to material found in an ancient wig-making workshop. FTIR showed that the skin, hair, and wig samples were treated with imported juniper resin had anti-bacterial and insecticidal properties. The skin and wig samples contained frankincense, and the hair sample contained henna. Discussion Combining the advantages of paleoradiology to the scientific investigations, provided enhanced comprehension of the mummy CIT8 and ancient Egyptian wig structure and material. CT scanning non-invasively showed the mummy's inner and exterior morphology, and estimated the age of death as 48 years. CT evaluated the mummification technique based on retained viscera and absence of embalming packs. The scientific tests revealed expensive imported embalming materials, contradicting the traditional belief that the non-removal of the viscera implied poor mummification, resulting in careless embalmers sealing the mouth. The widely opened mouth could be a result of facial expression of suffering before death, fixed by cadaveric spasm. The study also explores how rigor mortis, tissue decomposition, burial techniques, and postmortem alterations may contribute to a mummy's screaming appearance.